Health-related quality of life among patients with comorbid diabetes and kidney disease attending a codesigned integrated model of care: a longitudinal study. Issue 1 (6th January 2020) - Zimbudzi, Edward; Lo, Clement; Ranasinha, Sanjeeva; Teede, Helena; Usherwood, Tim; Polkinghorne, Kevan R; Fulcher, Greg; Gallagher, Martin; Jan, Steven; Cass, Alan; Walker, Rowan; Russell, Grant; et al.
Abstract : Objective: To evaluate the impact of an integrated diabetes and kidney disease model of care on health-related quality of life (HRQOL) of patients with comorbid diabetes and chronic kidney disease (CKD). Research design and methods: A longitudinal study of adult patients (over 18 years) with comorbid diabetes and CKD (stage 3a or worse) who attended a new diabetes kidney disease service was conducted at a tertiary hospital. A questionnaire consisting of demographics, clinical data, and the Kidney Disease Quality of Life (KDQOL-36) was administered at baseline and after 12 months. Paired t-tests were used to compare baseline and 12-month scores. A subgroup analysis examined the effects by patient gender. Multiple regression analysis examined the factors associated with changes in scores. Results: 179 patients, 36% of whom were female, with baseline mean±SD age of 65.9±11.3 years, were studied. Across all subscales, HRQOL did not significantly change over time (p value for all mean differences >0.05). However, on subgroup analysis, symptom problem list and physical composite summary scores increased among women (MD=9.0, 95% CI 1.25 to 16.67; p=0.02 and MD=4.5, 95% CI 0.57 to 8.42; p=0.03 respectively) and physical composite scores decreased among men (MD=−3.35, 95% CI −6.26 to −0.44; p=0.03). Conclusion: The HRQOL of patients with comorbid diabetes and CKD attending a new codesigned, integrated diabetes and kidney disease model of care was maintained over 12 months. Given that HRQOL is known to deteriorate over time in this high-risk population, the impact of these findings on clinical outcomes warrants further investigation.